Epistemologi algoritmik: Pergeseran pola pikir manusia dalam era kurasi digital - Abror, Muhammad Hikmal (Maliki Interdisciplinary Journal, 2025)
The digital era has introduced an information curation system governed by algorithms, fundamentally reshaping how humans think and perceive the world. The main issue that arises is the loss of cognitive freedom due to algorithmic dominance, which limits diversity of perspectives through the phenomena of filter bubbles and echo chambers. This article aims to examine the role of algorithms as epistemological agents and their impact on human thought, psychology, society, culture, and education. The approach employed is conceptual thinking supported by theoretical analysis, literature review, and critical reflection on digital curation phenomena in Indonesia. The findings reveal that algorithmic dominance fosters homogenization of thought, diminishes critical thinking ability, increases digital anxiety, and shifts the authority of knowledge from formal institutions to algorithmic influencers. As a proposed solution, this study emphasizes the importance of critical digital literacy, strengthening reflective education, ensuring algorithmic transparency, and promoting ethical technology design. Thus, the study highlights the urgency of building algorithmic epistemology awareness as an effort to preserve cognitive autonomy and safeguard diversity of perspectives in an increasingly curated information flow